Titanium superoxide catalyzed selective oxidation of phenols to p-quinones with aq. H2O2 - Dewkar, Gajanan; Shaikh, T. M.; Pardhy, S.; Kulkarni, S. S.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2005)
Titanium superoxide, a novel heterogeneous and readily accessible catalyst, is found to catalyze the selective oxidation of phenols to the corresponding 1,4-benzoquinones in preparative yields with aq. 30% H2O2 as oxidant under mild reaction conditions.

Titanium superoxide - a stable recyclable heterogeneous catalyst for oxidative esterification of aldehydes with alkylarenes or alcohols using TBHP as an oxidant - Dey, Soumen; Gadakh, Sunita K.; Sudalai, A. (Organic & Biomolecular Chemistry, 2015)
Titanium superoxide efficiently catalysed the oxidative esterification of aldehydes with alkylarenes or alcohols, under truly heterogeneous conditions, to afford the corresponding benzyl and alkyl esters in excellent yields. Mechanistic studies have established that this ``one pot'' direct oxidative esterification process proceeds through a radical pathway, proven by a FTIR spectral study of a titanium superoxide-aldehyde complex as well as spin trapping experiments with TEMPO. The intramolecular version of this protocol has been successfully demonstrated in the concise synthesis of 3-butylphthalide, an anti-convulsant drug.

Ti-superoxide catalyzed oxidative amidation of aldehydes with saccharin as nitrogen source: synthesis of primary amides - Kamble, Rohit B.; Mane, Kishor D.; Rupanawar, Bapurao D.; Korekar, Pranjal; Sudalai, A.; Suryavanshi, Gurunath (RSC Advances, 2020)
A new heterogeneous catalytic system (Ti-superoxide/saccharin/TBHP) has been developed that efficiently catalyzes oxidative amidation of aldehydes to produce various primary amides. The protocol employs saccharin as amine source and was found to tolerate a wide range of substrates with different functional groups. Moderate to excellent yields, catalyst reusability and operational simplicity are the main highlights. A possible mechanism and the role of the catalyst in oxidative amidation have also been discussed.